Exploring the influence of big five personality traits towards computer based learning (CBL) adoption - Farhad Khan, Muhammad Reza (Information Service Systems Innovation (ISSI) research group, Faculty of Computer Science and Information Systems, UTM, 2014)
It is widely accepted that the integration of modern Information and Communication Technologies (ICT) into the teaching-learning-process has enormous potentials especially after 4G technologies. Computer based learning (CBL) currently commonly used platforms to teach students not only in universities but also in the schools especially in developed countries. Underdeveloped countries are also trying to adopt CBL in their education system. Over the last decade most schools in developed countries around the world, ranging from pre to secondary schools have adopted the Computer Based Education systems (CBL) for their students. The purpose of this study is to develop a model based on previous studies done by other researchers, to find out the significant influence of personality over Technology Acceptance Model (TAM) in the area of technology adoption. This comprehensive study reviews previous research based on two basic categories technology adoption by teachers and students and personality in terms of technology adoption. Based on past studies a hypothesis has been developed to determine the influences between them. Perceived usefulness, perceived ease of use, attitude towards using and behavioral intention shows their influences over technology adoption. In addition, three personality items including openness, consciousness, and extraversion show strong influences over technology acceptance model.